Analisis Pelayanan Kuaplitas Apotek Franchise Terhadap Kepuasan Pelanggan: Studi Literature - Budi Satrio Wibowo; Dety Mulyanti (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
The pharmacy is a pharmaceutical service facility where pharmacists practice pharmacy. In this case the pharmacist is responsible for creating good service quality according to consumer expectations and satisfaction with services. Customer satisfaction is the key to the success of a business. Satisfied customers will become loyal customers. They will tend to make repeat purchases and become product promoters, which in turn will increase the pharmacy's revenue. The purpose of writing this scientific article is to find out and review from a theoretical point of view various literature and how to analyze the quality of franchise pharmacy services on customer quality. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review, namely the analysis of pharmacy quality on customer satisfaction is influenced by product quality, service quality, price, emotional factors and cost easiness. It was concluded that after being analyzed from various theories and literature, customer satisfaction is one indicator that is widely used in measuring the service quality of a product, both goods and services. Service quality can also affect customer loyalty directly and affect customer loyalty indirectly through satisfaction. Customer satisfaction is strongly influenced by the quality of pharmacy services. For pharmacies that provide pharmaceutical services, it is also necessary to improve service quality standards. One important aspect that needs to be considered to maintain the consistency of pharmaceutical services is to maintain the attributes of each dimension of service quality provided to customers. Customers will be satisfied if their needs are met according to their expectations. In addition, it is also necessary to evaluate each service activity.